CHALLENGES OF ONLINE LEARNING FACED BY EDUCATORS DURING THE ENDEMIC COVID-19: A REVIEW - Mohd Jidi, Munirah; Jamian, Nur Faithzah (Jurnal 'Ulwan, 2022)
The purpose of this paper is to critically review and synthesize the articles on issues or challenges faced by educators during online learning at higher institutions. For the past two years, we have been experiencing a pandemic called COVID-19, which is now endemic and people are slowly adjusting their lives to it. At higher institutions, faculty members are actively finding ways and solutions in making sure the teaching and learning process is kept on track. Educators have realized that face-to-face meetings are no longer applicable during this time, and they need to find another mode of communication promptly. Therefore, online classes, online webinars and all online platforms are options for educators in delivering lectures and disseminating information to their students. Nevertheless, there are challenges, obstacles and issues among educators. The educators’ readiness, acceptance of technology among them, and many more are issues that need to be put into consideration in implementing online classes. The review will give a holistic understanding of the online learning challenges among educators for future researchers and aid to identify the research gap.